1970
DOI: 10.13057/biodiv/d070119
|View full text |Cite
|
Sign up to set email alerts
|

Effect of three different nitrogen fertilizers on several vegetable crops

Abstract: Applications of three different sources of N fertilizers (urea, compost from slaughter house and chicken manure compost) on vegetable crops (tomato, okra and spinach) were conducted in the green house of Research Institute for Food Crop Biotechnology, Bogor from August of 1999 to April of 2000. Treatments consisted of: (i) without fertilizer, (ii) 5 g N/pot of urea, (iii) 10 g N/pot of slaughter house compost, (iv) 10 g N/pot of chicken manure compost, (v) 5 g N/pot of urea + 10 g N/pot of slaughter house comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 1 publication
0
9
0
Order By: Relevance
“…According to Adil et al (2006), the application of organic fertilizer could improve soil fertility. Asiah (2006) added that the application of organic materials could increase yield productivity and reduce the intensity of pest and disease.…”
Section: Introductionmentioning
confidence: 99%
“…According to Adil et al (2006), the application of organic fertilizer could improve soil fertility. Asiah (2006) added that the application of organic materials could increase yield productivity and reduce the intensity of pest and disease.…”
Section: Introductionmentioning
confidence: 99%
“…A study conducted by Hernandez et al (2014), showed the lower yields observed in the soils treated only with compost is probably due to nutrient limitation, mainly N. Combination use of organic and mineral fertilization improved the effect on yield compared to the use of mineral fertilization alone, although differences were not always statistically significant. Another study conducted by Adil et al (2006) showed that tomato fertilized with compost alone or in combination with urea resulted in significant total fruits than those control. A further study such as nutrient analysis on kangkung biomass and tomato fruit to determine the effect of various type of compost on nutrient content has to be done towards the organic farming (Figure 4).…”
Section: Vegetable Plantmentioning
confidence: 99%
“…Not only is this productivity often short-lived, but the consistent use of chemicals such as these threaten the health of farmers and ultimately, the health of the surrounding ecosystem [66,67]. The prolonged use of chemical fertilizers changes the pH of soil, causing it to become too acidic, and can also impair soil fertility [68,69]. The reversal of soil acidification and restoration of soil fertility is possible through the use of natural fertilizers [68] but requires not only the commitment of the farmer/s in question, but every farmer in the area due to the possibility of run-off.…”
Section: Organic Alternativesmentioning
confidence: 99%
“…The prolonged use of chemical fertilizers changes the pH of soil, causing it to become too acidic, and can also impair soil fertility [68,69]. The reversal of soil acidification and restoration of soil fertility is possible through the use of natural fertilizers [68] but requires not only the commitment of the farmer/s in question, but every farmer in the area due to the possibility of run-off. Natural fertilizers, such as chicken manure, are already used due to their wide availability and low cost.…”
Section: Organic Alternativesmentioning
confidence: 99%